“Efecto de la posición y profundidad en la siembra de estacas de yuca (manihot esculenta crantz) variedad “arpu, rumu” y su rendimiento en el bajo mayo” - Chota Salas, Hugo Ruel (2004)
In an experiment carried out in a soils entisol of free texture, located in the Morales of district, San Martin of County and Department; yucca stake was sowed to five, ten and fifteen centimeters deep and in three different positions: horizontal, inclined and vertical. The results revealed highly significant differences. The study demonstrated that the plantation depth affects considerably to the production of roots reserve, the germinating of yolks, plant height, in connection with the yields obtained in the experiment, the treatments vertical of five, ten and fifteen centimeters were the most favorable registering 37 .87; 36.87 and 36.00 t/ha. All the studied treatments showed utility that varied 4 340.82 to 7 469.04 new suns for hectare. The treatments 7, 9 and 8 were those that obtained a bigger net utility of 7 469.04, 7 045.64 and 6 845.74 with relationship cost / beneficent of 1.92, 1.75 and 1.73 %. The variation in the utility was due to the manpower used in the crop, packing and transport.